2023
DOI: 10.3390/metabo13030414
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity and the Cryptic Language of the Microbiota: Metabolomics’ Upgrading

Abstract: The growing obesity epidemic in childhood is increasingly concerning for the related physical and psychological consequences, with a significant impact on health care costs in both the short and the long term. Nonetheless, the scientific community has not yet completely clarified the complex metabolic mechanisms underlying body weight alterations. In only a small percentage of cases, obesity is the result of endocrine, monogenic, or syndromic causes, while in much more cases, lifestyle plays a crucial role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…Therefore, the implications of pediatric obesity go beyond childhood into adulthood, increasing considerably the health-related costs. Other important long-term complications of obesity consist of chronic inflammation, which was proven to be present also in children [46], dyslipidemia, hypertension, hyperuricemia, obstructive sleep apnea, nonalcoholic fatty liver disease, and even cancer [6]. Although genetic background plays a major role in predisposing individuals to obesity, obesogenic factors such as eating habits, sedentary lifestyle, and urbanizations seem to be the ones that decide, finally, whether an individual will become obese or not [16].…”
Section: Obesity Microbiota and Prebiotics Probiotics And Synbioticsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the implications of pediatric obesity go beyond childhood into adulthood, increasing considerably the health-related costs. Other important long-term complications of obesity consist of chronic inflammation, which was proven to be present also in children [46], dyslipidemia, hypertension, hyperuricemia, obstructive sleep apnea, nonalcoholic fatty liver disease, and even cancer [6]. Although genetic background plays a major role in predisposing individuals to obesity, obesogenic factors such as eating habits, sedentary lifestyle, and urbanizations seem to be the ones that decide, finally, whether an individual will become obese or not [16].…”
Section: Obesity Microbiota and Prebiotics Probiotics And Synbioticsmentioning
confidence: 99%
“…Childhood obesity, a real pandemic, represents, in fact, a major public health problem worldwide, with an increasing trend in prevalence during the last decades, especially in developed countries [1][2][3][4][5]. Due to its associated short-and long-term complications, it carries an important burden not only for health services, but also for society, since it is associated with both psychosocial problems like bullying, resulting in school absences and consequent poor school results, and organic conditions such as metabolic syndrome with insulin resistance, cardiovascular disorders, hypertension, dyslipidemia, non-alcoholic fatty liver disease, obstructive sleep apnea, and even neoplasia [6][7][8][9][10][11][12][13][14]. According to the most recent reports of the World Health Organization (2020), 39 million children under the age of 5 years suffer from either overweight or obesity, with an impressive increase between 5 and 19 years, reaching up to 340 million cases [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our Past study indicated that CC motif chemokine ligand 3 (CCL3) is highly expressed in the intestinal lesions of NEC patients, mediates macrophage in ltration and induces M1-type polarization, thus participating in the occurrence and development of NEC 11,12 . However, its utility as a biomarker for early detection of NEC has not been explored.…”
Section: Introductionmentioning
confidence: 99%